PENGARUH MEDIASI KEPUASAN KERJA PADA HUBUNGAN WORK-FAMILY CONFLICT DAN KOMITMEN ORGANISASIONAL - Veronika Agustini Srimulyani; Ardhika Vicki Prasetian (Universitas Negeri Yogyakarta, 2014)
The aim of this study is to examine whether work family conflict affects the organizational commitment mediated by job satisfaction in the lecturer profession. The populationin this studyis a lecturer instructural officerlevelcoursesat private higher institution in Madiun. The research subjects were 45 lecturerstructurallevelofficials. The data analyzed by using simple and multiple regression technique, using SPSS 17.0 for windows.The result of path analysis indicate that:1) workfamily conflict have a direct effect on job satisfaction significantly; 2) workfamily conflict have a direct effect on organizational commitment significantly; 3) job satisfaction have a direct effect on organizational commitment significantly; 4) job satisfaction mediate the effect of workfamily conflict on organizational commitment significantly.